Fast and cost‐efficient species identification of Atlantic salmon ( Salmo salar L.), brown trout ( Salmo trutta), and their hybrids using a single SNP marker - Aykanat, Tutku; Balatsou, Athina; Kähkönen, Kirsi; Syrjänen, Jukka T.; Janhunen, Matti; Leinonen, Tuomas; Prokkola, Jenni M.; Norrgård, Johnny R.; Piccolo, John J. (Journal of Fish Biology, 2024)
Abstract A workflow for developing a cost‐ and time‐efficient, single nucleotide polymorphism (SNP)‐based assay for species and hybrid identification is described. In a reference set ( n = 46), the developed assay identified individuals of two closely related species, the Atlantic salmon ( Salmo salar L., n = 23) and brown trout ( Salmo trutta , n = 23), with 100% accuracy. Furthermore, species and hybrid identification using field‐collected embryos had 98.1% concordance (155/158) to more expensive and time‐consuming methods that utilized multiple SNP markers. The method can be integrated into management and conservation plans to quantify species' spawning distribution and hybridization rates.